Clinical Characteristics of Trigeminal Neuralgia Patients at Dr. Hasan Sadikin General Hospital Bandung Indonesia in 2010–2012 - Sri Hudaya Widihastha; Henny Anggraini Sadeli; Arifin Sunggono (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Trigeminal neuralgia is a frequently found craniofacial neuralgia. The clinical characteristics of trigeminal neuralgia patients at Dr. HasanSadikin General Hospital, Bandung, Indonesia has never been described before. This study conducted an overview of clinical characteristics of trigeminal neuralgia to determine the characteristic features of trigeminal neuralgia.Methods: This was a non-experimental study using secondary data with a retrospective descriptive method. Data related to medical records of 76 patients with trigeminal neuralgia was collected over a period of 2010 to 2012, treated at Dr.HasanSadikin General Hospital Bandung, Indonesia. Results: Mean age was 57.6 years (range 11 to 84 years), no significant difference in gender (male:females 51.3%:48.7%). Chewing and swallowing was reported as triggering stimuli to 42 (55%) patients. Two patients (2.7%) had suffered pain on bilateral side of the face, 46 (60.5%) patients the right side, and 28 patients (36.8%) on the left side. Pain on maxillary nerve division was found in 58 (76.3%) patients. Sixty one of the patients (80%) received Carbamazepine.Conclusions: The peak age was between the fifth and sixth decades of life with equal representation of male to female incidence. Right side and the maxillary division was found to be the most frequently site of pain. Chewing and swallowing was reported to be the most frequent triggering stimuli and most of patients received Carbamazepine as therapy. [AMJ.2017;4(1):47–51]DOI: 10.15850/amj.v4n1.1020